Successful Management of High-Risk Acute Pulmonary Embolism in Patients with Undetected Hepatocellular Carcinoma: A Case Report - zunardi, Lutfi hafiz; Kurnianingsih, Novi; Martini, Heny (Heart Science Journal, 2023)
AbstractBackground: Acute pulmonary embolism (PE) as the earliest manifestation of hepatocellular carcinoma (also known as HCC) is an extremely uncommon discovery and a very uncommon illness. It is a serious condition that can be life-threatening and has high morbidity and mortality rates. Despite the high prevalence of PE, the diagnosis is still challenging, mainly due to the unpredictability of symptoms and physical signs and the unexplained cause. The stratification of acute pulmonary embolism is important because it determines the right steps in decision-making.Case Illustration: A 45-year-old man presented to the ER at a private hospital with complaints of sudden shortness of breath after taking a bath. His family brought him to the private hospital 30 minutes after the onset. He came with desaturation and shock conditions. He was assessed as having an acute coronary syndrome (ACS). He got loaded with dual antiplatelets and was referred to our hospital. Because the patient's complaint is not angina but sudden shortness of breath accompanied by desaturation, we rule out ACS. We considered the possibility of a pulmonary embolism, so we performed bedside TTE in the ER and found RV dysfunction and McConnell's sign leading to acute PE. We continued with the CT examination and found a thrombus in the pulmonary artery. We assessed patients with high-risk pulmonary embolism and performed thrombolysis with rTPA. The patient's complaints gradually improved. Initially, we suspected unprovoked PE because we did not find a clear trigger, such as malignancy, prolonged bedriddenness, recent surgery, or old age. We accidentally found HCC from the patient's CTPA evaluation, and HBSAG was reactive.Conclusion: Every case of dyspnea that shows up at an emergency room should have acute PE taken into consideration in the differential diagnosis. In patients with suspected PE without obvious risk factors, we can use CT to triple-rule out ACS, Aortic dissection, and pulmonary embolism. Patients treated with thrombolytic therapy show rapid improvement, which may lead to a lower rate of mortality and morbidity.